CHILD ABUSE IN DAVE PELZER'S A CHILD CALLED IT: A SOCIOLOGICAL APPROACH - SUMIYATI., ENDANG (2011)
This research paper elaborates child abuse that is reflected in Dave Pelzer memoir, which is analyzed through sociological approach. The objectives of the research are to analyze the memoir based on its structural elements and to analyze the memoir based on the sociological approach, by identifying the relation between the memoir and the social background of American society in the last twentieth century. This research paper belongs to a qualitative research. The sources of the data come from both primary data source, which is A Child Called It memoir and secondary data sources are information about the author's biography, websites about the memoir, the social background of American society in the last twentieth century and theory of sociological. The method to analyze the data is descriptive analysis. Having analyzed the memoir, the researcher comes to the following conclusion as follows. Firstly, based on the structural analysis, it is evident that in this memoir A Child Called It, Dave Pelzer conveys a moral message that some children are not brought up properly because of unstable parents. Secondly, based on the sociological analysis it is clear that in this memoir Dave Pelzer not only portrays the social phenomena in which a child becomes the victim of abusive parents, but also the society that ignores the right of the children to be brought up properly.